Class Mapping of Tsunami's Risk using Global Positioning Geodetic System in Bengkulu University's Environment - Umaya, Umaya; Mayub, Afrizal; Johan, Henny; Farid, Muchammad; Wardana, Rendy Wikrama (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
Bengkulu University is located in the coastal area precisely in Muara Bangka Hulu sub-district of Bengkulu City, which is one of the sub-districts bordering the coastline. Areas or regions bordering the coastline have a higher level of tsunami hazard compared to areas or regions far from the coastline. The marking of the evacuation point area in the Bengkulu University environment has not adjusted to the disaster mitigation parameters. The purpose of this research is to analyse and map the tsunami hazard class at Bengkulu University in a preventive mitigation effort as well as a consideration for future policies. Primary data measurements used Geodetic GPS devices and were analysed using GAMIT and GLOBK 10.6 software. While secondary data obtained from geospatial information agencies and DEMNAS were analysed using arcgis software. Based on the results of the analysis, it is known that the environment of Bengkulu University as a whole has 3 classes of hazard zones including high hazard class, medium hazard class, and low hazard class.